2015
DOI: 10.1039/c4tx00211c
|View full text |Cite
|
Sign up to set email alerts
|

A modified weight-of-evidence approach to evaluate the allergenic potential of food proteins

Abstract: Schematic interpretation of a modified weight-of-evidence approach for evaluating the allergenic potential of food proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…This indicated that TM induced mast cells to release a large number of cytokines and proteases, which significantly enhanced intestinal permeability and seriously destroyed the physiological function of mucosa. 36 However, the extent of histopathological changes in the spleen, lung, and jejunum of mice administered with TM and OVA by gavage was significantly lighter than those observed with intraperitoneal injection. In other words, it was suggested that gastrointestinal digestion may weaken the immunogenic potential of TM and reduce hypersensitivity in mice to some extent.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This indicated that TM induced mast cells to release a large number of cytokines and proteases, which significantly enhanced intestinal permeability and seriously destroyed the physiological function of mucosa. 36 However, the extent of histopathological changes in the spleen, lung, and jejunum of mice administered with TM and OVA by gavage was significantly lighter than those observed with intraperitoneal injection. In other words, it was suggested that gastrointestinal digestion may weaken the immunogenic potential of TM and reduce hypersensitivity in mice to some extent.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…The villi of jejunum exhibited severe rupturing and exfoliation, with a large number of inflammatory cell infiltration and goblet cell proliferation. This indicated that TM induced mast cells to release a large number of cytokines and proteases, which significantly enhanced intestinal permeability and seriously destroyed the physiological function of mucosa . However, the extent of histopathological changes in the spleen, lung, and jejunum of mice administered with TM and OVA by gavage was significantly lighter than those observed with intraperitoneal injection.…”
Section: Resultsmentioning
confidence: 96%
“…And so far, the evaluation of the allergenicity of the BLG-free milk has not yet been investigated. For evaluating the allergenic potential of food proteins, animal models are a useful tool for a direct assessment of the sensitizing potential of food 22 , such as the Balb/c mice model 23 25 . One of the important characteristics responsible for the allergenicity of food proteins is their stability against pepsin digestion 26 .…”
Section: Introductionmentioning
confidence: 99%